2003
DOI: 10.1002/em.10189
|View full text |Cite
|
Sign up to set email alerts
|

Use of the comet assay for studying environmental genotoxicity: Comparisons between visual and image analyses

Abstract: In order to evaluate the applicability of different measurement parameters employed in the comet assay for analyzing environmental samples, fish hepatoma (RTH-149) cells were exposed to concentrations of the model genotoxic agent hydrogen peroxide (H(2)O(2); 1, 5, and 10 microM) and to five water samples from sites along the Kishon River, the most polluted river in Israel. DNA damage was scored in parallel by visual and computer-image (Viscomet) analyses using 12 different parameters. Each parameter exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 50 publications
0
16
0
2
Order By: Relevance
“…41 Since the introduction of the alkaline modification using this assay, 42,43 there have been studies using this method to visualize DNA degradation. 44, 45 Singh et al 43 found that the comet moments are the most sensitive indices of DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Since the introduction of the alkaline modification using this assay, 42,43 there have been studies using this method to visualize DNA degradation. 44, 45 Singh et al 43 found that the comet moments are the most sensitive indices of DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…The comet assay, a gel electrophoresis technique, is a sensitive technique for evaluating DNA damage. 41 Since the introduction of the alkaline modification using this assay, 42,43 there have been studies using this method to visualize DNA degradation. 44,45 Myonuclei DNA damage also was assessed using a gel electrophoresis assay (comet).…”
Section: Methodsmentioning
confidence: 99%
“…After electrophoresis, the slides were washed three times with neutralization buffer (0.4M Tris, pH 7.5). All preparative steps were conducted in yellow light to prevent occurance of additional DNA damage (Avishai et al, 2003;Tice et al, 2000;Velma and Tchounwou, 2010).…”
Section: Comet Assaymentioning
confidence: 99%
“…The cell images were projected onto a high resolution Heper-HAD TM (Sony, Tokyo, Japan) CCD camera [8 bits (Applitec, Holon, Israel; LIS-700)] and analyzed with Viscomet image analysis software using the MV Delta frame grabber (Matrix Vision, Oppenweiler, Germany). DNA damage in each treatment was measured in duplicates of 50 cells each, using two highly informative parameters (Avishai et al, 2003): tail extent (sum of all distances of each horizontal scan line from the first signal pixel to the last signal pixel divided by number of scan lines) and tail extent moment (tail length ϫ percentage tail DNA). Controls (algal-free cells, animal cells, holobionts) were handled as experimental cells, but without UVR treatment.…”
Section: The Comet Assaymentioning
confidence: 99%
“…The coral species used in this study is the Indo-Pacific, shallow water branching form, Stylophora pistillata. UV-induced DNA damage and DNA repair levels were evaluated by the single cell gel electrophoresis assay, also known as the comet assay, one of the most reliable and sensitive methods for evaluating DNA damage induced in individual cells by various agents (Mitchelmore and Chipman, 1998;Avishai et al, 2003;Reinhardt et al, 2003).…”
mentioning
confidence: 99%